Study guides

☆☆

Q: What is the square root of 24 minus square root of 6?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

8*6**0.5 - 2*24**0.5 24**0.5= 4**0.5 * 6**0.5 24**0.5= 2*6**0.5 8*6**0.5 - 2*2*6**0.5 8*6**0.5 - 4*6**0.5 4*6**0.5

plus or minus 6

sqrt(24) / sqrt(6) = sqrt(24/6) = sqrt(4) = Â±2

Could be +6, -6, +16, or -16.

The numbers are: 6 plus square root of 27 and 6 minus square root of 27

Related questions

9 square root 4 minus 12 square root 4 = -6

Square root 400 - square root 196 = 6

I assume you don't want a calculator answer, where you simply plug it into you're calculator and get the answer (in which case, it would be 1.54919333848....etc) however, the best solution would be radical(12)/radical(5) first, convert 2.4 into a fraction. this will make it 24/10. then find the square roots of both the numerator and the denominator. radical(24)/radical(10) this can be simplified into radical(12)radical(2)/radical(5)radical(2) the radical(2)'s cancel out, and we're left with radical(12)/radical(5).

X2+5x-6. a=1, b=5, and c=-6 The formula is: -b plus or minus the square root of b squared minus 4ac all over 2a. -b+square root of b2-4ac ---- 2a -5 plus or minus the square root of 5 squared minus 4(1)(-6) -5 plus or minus the square root of 25-4(-6) -5 plus or minus the square root of 25+24 -5 plus or minus the square root of 49 -5 plus or minus 7 Here is where you split into two different answers: Number 1: -5 plus 7= 2 Number 2: -5 minus 7= -12 Your answer is X=2, -12

The idea is to take any perfect square out of the square root sign. root(24) = root(4 x 6) = root(4) x root(6) = 2 x root(6).The idea is to take any perfect square out of the square root sign. root(24) = root(4 x 6) = root(4) x root(6) = 2 x root(6).The idea is to take any perfect square out of the square root sign. root(24) = root(4 x 6) = root(4) x root(6) = 2 x root(6).The idea is to take any perfect square out of the square root sign. root(24) = root(4 x 6) = root(4) x root(6) = 2 x root(6).

Yes and x = 2+square root of 6 or x = 2-square root of 6

It is the square root of 8

8*6**0.5 - 2*24**0.5 24**0.5= 4**0.5 * 6**0.5 24**0.5= 2*6**0.5 8*6**0.5 - 2*2*6**0.5 8*6**0.5 - 4*6**0.5 4*6**0.5

Yes. √6 + √24 = √6 + √(4 x 6) = √6 + 2√6 = 3√6 (= √54)

square root of 36 = 6 6 multiplied by 6 = 36 formula -> x2 = 36 (take square root of both sides) -> x = plus/minus 6

6

plus or minus 6

People also asked